The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jsr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive coronary plaque assessment in patients with obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is associated with an increased risk of cardiovascular disease. Previous studies have assessed the relationship between OSA and coronary artery disease (CAD) using coronary artery calcium score (CAC) measurements. However, limited data are available regarding the association of OSA with non‐calcified plaque burden. We therefore aimed to assess the relationship between CAD severity as assessed by coronary computed tomography angiography (CTA) and OSA. Forty‐one adult subjects (59 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
2
10
0
2
Order By: Relevance
“…Of note, the prevalence of cerebrovascular and cardiovascular disease in both populations was higher compared to the general population (around 10%) [33]. However, both values were still lower compared to the asymptomatic coronary plaque burden (80%) as reported in a previous study [34]. Apart from risk factors accounted for in our study, additional factors including alcohol consumption, diet, exercise and air pollution could contribute to the observed differences.…”
Section: Discussionsupporting
confidence: 46%
“…Of note, the prevalence of cerebrovascular and cardiovascular disease in both populations was higher compared to the general population (around 10%) [33]. However, both values were still lower compared to the asymptomatic coronary plaque burden (80%) as reported in a previous study [34]. Apart from risk factors accounted for in our study, additional factors including alcohol consumption, diet, exercise and air pollution could contribute to the observed differences.…”
Section: Discussionsupporting
confidence: 46%
“…1 The relationship between sleep duration and metabolic syndrome. The forest plot summarised the ORs (95% CI) of different sleep durations for baseline or new onset metabolic syndrome apnea (OSA), a cardiovascular risk factor [28], was not available and thus not considered in this study. However, the use of objective methods (like polysomnography) to accurately measure the OSA is usually not feasible in large studies of general populations, which is a common limitation of sleep-related epidemiological studies [9].…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…However, 14 patients (19%) of the overall cohort indicated that someone had observed them to stop breathing while sleeping, suggesting a potential under-diagnosis of OSA among cardiology patients. Additionally, a recent study in a population of patients with mild OSA symptoms using coronary computed tomography angiography found no significant correlation between calcification measured by the calcium artery score and OSA [30]. The study did, however, find an association between calcification and OSA, when calcification was measured by segment involvement score and segment stenosis score.…”
Section: Sleep and Readmissionsmentioning
confidence: 69%